Dentin bonding systems: From dentin collagen structure to bond preservation and clinical applications. Issue 1 (January 2018) - Breschi, Lorenzo; Maravic, Tatjana; Cunha, Sandra Ribeiro; Comba, Allegra; Cadenaro, Milena; Tjäderhane, Leo; Pashley, David H.; Tay, Franklin R.; Mazzoni, Annalisa
Abstract: Objectives: Efforts towards achieving durable resin–dentin bonds have been made for decades, including the understanding of the mechanisms underlying hybrid layer (HL) degradation, manufacturing of improved adhesive systems, as well as developing strategies for the preservation of the HL. Methods: This study critically discusses the available peer-reviewed research concerning the formation and preservation of the HL, the mechanisms that lead to the degradation of the HL as well as the strategies to prevent it. Results: The degradation of the HL occurs through two main mechanisms: the enzymatic degradation of its collagen fibrils, and the leaching of the resin from the HL. They are enabled by residual unbound water between the denuded collagen fibrils, trapped at the bottom of the HL. Consequently, endogenous dentinal enzymes, such as the matrix metalloproteinases (MMPs) and cysteine cathepsins are activated and can degrade the denuded collagen matrix. Strategies for the preservation of the HL over time have been developed, and they entail the removal of the unbound water from the gaps between the collagen fibrils as well as different modes of silencing endogenous enzymatic activity. Significance: Although there are many more hurdles to be crossed in the field of adhesive dentistry, impressive progress has been achieved so far, and the vast amount of available research on the topic is an indicator of the importance of this matter and of the great efforts of researchers and dental material companies to reach a new level in the quality and longevity of resin–dentin bonds.